The Impacts of International Rape Laws Upon Official Rape Rates - Chon, Donsoo (International journal of offender therapy and comparative criminology, 2021)
Relying on the official rape rates, previous cross-national researchers found a significant and positive relationship between gender equality and the rates of reported rapes, and they used such findings as supporting evidence of the backlash hypothesis that increased gender equality leads to augmented violence against females. However, such a conclusion may be faulty because of the contested validity and reliability of the official rape rate. This study examined how the variation in a comprehensive legal definition of rape is associated with the rates of reported rapes across 74 countries by using the rates of reported rapes from the United Nations Office of Drugs and Crime. The regression analysis suggests that the comprehensive legal definition of rape, more than a country’s gender equality and developmental level, is related to the official rape rate. A country records a high official rape rate when the country includes a broad range of sexual assaults in the category of rape crime, suggesting a reevaluation of the existing studies on this topic.